Bidirectional recovery patterns of Mojave Desert vegetation in an aqueduct pipeline corridor after 36 years: I. Perennial shrubs and grasses. (January 2016) - Berry, Kristin H.; Weigand, James F.; Gowan, Timothy A.; Mack, Jeremy S.
Abstract: We studied recovery of 21 perennial plant species along a severely disturbed aqueduct corridor in a Larrea tridentata - Ambrosia dumosa plant alliance in the Mojave Desert 36 years after construction. The 97-m wide corridor contained a central dirt road and buried aqueduct pipeline. We established transects at 0 m (road verge), 20 m and 40 m into the disturbance corridor, and at 100 m in undisturbed habitat (the control). Although total numbers of shrubs per transect did not vary significantly with distance from the verge, canopy cover of shrubs, species richness, and species diversity were higher in the control than at the verge and other distances. Canopy cover of common shrubs ( Ericameria nauseosa, Ambrosia salsola, A. dumosa, L. tridentata, Grayia spinosa ) and perennial grasses ( Elymus elymoides, Poa secunda ) also varied significantly by location. Discriminant analysis clearly separated the four distances based on plant composition. Patterns of recovery were bidirectional: secondary succession from the control into the disturbance corridor and inhibition from the verge in the direction of the control. Time estimated for species composition to resemble the control is dependent on location within the disturbance corridor and could be centuries at the road verge. Our findings have applications to other deserts. Highlights: We studied succession in Mojave Desert shrubs and grasses 36 years after disturbance. Two types of succession were underway in the 97-m wide linear disturbance corridor. Secondary succession is occurring from edges of the disturbance inward. Inhibition is occurring within the central corridor of the disturbance at a road verge. Time estimates for recovery are location dependent in the disturbance corridor.